The Effectiveness of Interactive Video-Based Motion Learning on Motor Coordination and Visual Literacy (Symbols) in Early Childhood - Siti Labiba Kusna; Endang Puspitasari (Journal of Childhood Development, 2025)
The development of motor coordination and visual literacy skills in early childhood requires innovative learning stimulation that aligns with children's learning characteristics. However, learning activities in early childhood education institutions still predominantly use conventional methods that lack movement activities and interactive visual media. This study aims to determine the effectiveness of interactive video-based motion learning on the motor coordination and visual symbol literacy of children aged 5–6 years. This study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of children aged 5–6 years who were divided into experimental and control groups. Data collection techniques included observation, documentation, and performance assessment. The research instruments were motor coordination observation sheets and visual symbol literacy indicators. Data analysis was conducted using descriptive statistics and t-tests. The results showed that interactive video-based motion learning was effective in improving children's motor coordination and visual symbol literacy. The hypothesis testing results showed a significance value of 0.000 < 0.05, indicating that Ha was accepted and H0 was rejected. Children became more active, focused, able to follow movement instructions, recognize visual symbols, and coordinate body movements better during the learning process. This study contributes to understanding the integration of movement-based learning and digital media in early childhood education. The findings show that interactive video-based motion learning effectively improves children's motor coordination and visual symbol literacy. Practically, it can be used as an innovative strategy to enhance children's physical and cognitive development in classroom learning.